Behaviour of indirect immunofluorescence test and some cerebrospinal parameters in neurocysticercosis - Amauri Braga Simonetti; Jorge Teixeira (Arquivos de Neuro-Psiquiatria)
Cerebrospinal fluid from 53 patients with clinical evidence of neurocysticercosis and 11 who suffered from several diseases were studied to evaluate the behaviour of indirect immunofluorescence test and some parameters of routine analysis. In neurocysticercosis there were pleocitosis in 88.7% of cases, eosinophilorrachia in 60.3%o, hyperproteinorrachia in 71.7% and hypoglucorrachia in 13.2%. The indirect immunofluorescence test was positive in 19.2% of cases but false-positive results were found when the samples showed xanthochromia or erythrocyte contamination. The authors discuss their results in comparison with those in literature and conclude that the immunofluorescent test is sensitive and useful in diagnosis of neurocysticercosis, except when the interferents previously mentioned are present.